Brazil and the G-20: Domestic Pressures and the Construction of the Negotiating Position in the Doha Round of the WTO - Ramanzini Junior, Haroldo; Mariano, Marcelo Passini [UNESP] (Kluwer Law Int, 2013)
The purpose of this text is to examine the actions taken by the Brazilian Government in the G-20 coalition, within the context of the Doha Round of the WTO, the main focus being to understand the domestic decision-making process that led to the formulation of Brazil's positions within the coalition. We seek to understand to what extent Brazilian foreign policy has been influenced by domestic pressures with regard to Brazil's positions within the G-20, as well as to assess the influence exerted by domestic governmental and non-governmental actors on the process of formulation and implementation of the Brazilian strategy in the G-20 coalition during the 2003-2008 period. We maintain that the way Brazil acted in the G-20 is related both to the internal process by which the country's negotiating position was built and to the limits established by the very logic of the negotiations. The decision-making process that built the Brazilian position has been an important variable in the maintenance of the coalition.